Maternal adiposity negatively influences infant brain white matter development. (May 2015) - Ou, Xiawei; Thakali, Keshari M.; Shankar, Kartik; Andres, Aline; Badger, Thomas M.
<x xml:space="preserve">Abstract</x> Objective To study potential effects of maternal body composition on central nervous system (CNS) development of newborn infants. Methods Diffusion tensor imaging (DTI) was used to evaluate brain white matter development in 2‐week‐old, full‐term, appropriate for gestational age (AGA) infants from uncomplicated pregnancies of normal‐weight (BMI < 25 at conception) or obese ( BMI = 30 at conception) and otherwise healthy mothers. Tract‐based spatial statistics (TBSS) analyses were used for voxel‐wise group comparison of fractional anisotropy (FA), a sensitive measure of white matter integrity. DNA methylation analyses of umbilical cord tissue focused on genes known to be important in CNS development were also performed. Results Newborns from obese women had significantly lower FA values in multiple white matter regions than those born of normal‐weight mothers. Global and regional FA values negatively correlated (P < 0.05) with maternal fat mass percentage. Linear regression analysis followed by gene ontology enrichment showed that methylation status of 68 CpG sites representing 57 genes with GO terms related to CNS development was significantly associated with maternal adiposity status. Conclusions These results suggest a negative association between maternal adiposity and white matter development in offspring.